European Health Data Space : A breakthrough in user control over health data in wellness apps? - Holmberg, Petra (The European Health Data Space : Examining A New Era in Data Protection, 2025)
The European Health Data Space (EHDS) marks a pivotal moment in regulating wellness applications within the European Union. This chapter examines the implications of the EHDS for user control over electronic health data processed through wellness apps, scrutinising the regulatory frameworks provided by both the General Data Protection Regulation (GDPR) and the EHDS. Despite the GDPR’s stringent requirements for valid consent, research reveals widespread non-compliance among wellness apps. The EHDS introduces a labelling system for interoperable wellness apps, aiming to ensure security, transparency and interoperability. However, this chapter identifies several risks and shortcomings, including ambiguity in definitions, lack of clarity on registration processes and inadequate oversight. The EHDS falls short of adequately addressing user consent and transparency issues within wellness applications. Given these concerns, this chapter strongly advocates for embedding valid consent for initial data acquisition by wellness applications as a fundamental change to enhance user control over their data. This is a crucial measure in empowering users and effectively protecting their privacy rights. The chapter proposes recommendations for the European Commission and member states to implement in the EHDS. By addressing these challenges, legislators can ensure that the EHDS fosters innovation while prioritising data protection and user control.